Zirconia nanoparticles prepared by laser vaporization as fillers for dental adhesives - Lohbauer, Ulrich; Wagner, Andrea; Belli, Renan; Stoetzel, Christian; Hilpert, Andrea; Kurland, Heinz-Dieter; Grabow, Janet; Mueller, Frank A. (Acta Biomaterialia, 2010)
Zirconia nanoparticles prepared by laser vaporization were incorporated into the primer or into the adhesive of a commercial adhesive system in order to evaluate its effect on bond strength to dentin. Zirconia nanoparticles (20-50 nm) were prepared using a particular laser vaporization technique and incorporated into the primer (P) or into the adhesive (A) of the Adper Scotchbond Multi-Purpose (SBMP) system at 5, 10, 15 and 20 wt.% by means of mechanical mixing (stirring) and ultrasonication. Control (unfilled) and experimental groups (filled) were applied, according to the manufacturer's instructions, onto flat mid-coronal human dentin. Composite crowns were built up, stored in distilled water for 24 h at 37 °C and cut into 0.65 ± 0.05 mm2 beams following a non-trimming microtensile technique. Specimens were fractured in tension using a universal testing machine (Zwick) and examined by scanning electron microscopy for fractographic analysis. Microtensile bond strength (μTBS) data were analyzed using a two-way ANOVA and modified LSD test at α = 0.05. Analysis of the nanofiller distribution and ultramorphological characterization of the interface were performed by transmission electron microscopy (TEM). Zirconia nanoparticle incorporation into the primer or into the adhesive of SBMP significantly increased μTBS to dentin. Filler concentration only affected μTBS significantly in the P group. Statistically significant differences between groups P and A occurred only at 20 wt.% filler content, with a significantly higher μTBS in group P. TEM micrographs revealed nanoparticle deposition on top of a hybrid layer when incorporated into the primer, whereas they remained dispersed through the adhesive layer in group A. Zirconia nanoparticles incorporation into SBMP increased bond strength to dentin by reinforcing the interface adhesive layer. Nanofiller incorporation into the primer solution showed a tendency of increasing bond strength with increasing concentration. At high concentrations (20 wt.%) nanofiller incorporation was more efficient in increasing bond strength if incorporated in the primer solution. Adding nanofillers to the primer and to the adhesive solutions resulted in different particle distributions at the interface. © 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Dentin bonding; Laser vaporization; LAVA; Nanoparticle; Zirconia